Attitudes and perceptions of gesturing among early childhood educators in Singapore - Ong, Dylan Lip Khuan (Nanyang Technological University, 2024)
Early childhood education (ECE) has been shown to have lasting impacts on development and life outcomes1. In Singapore, a strong focus on ECE has emerged over the recent decades, emphasizing the importance to provide quality ECE to children2. As such, it is imperative to explore ways to improve the quality of ECE in Singapore.